Réponses

2014-09-10T16:47:56+02:00
A = -22 + ( 10 - 36 x 2/9 )
= -22 + ( 10 - 8 )
= -22 + 2
= -20

B = 72 : 8 - 5 x 2
= 9 - 10
= -1

C = (-5)^3 + 27 x (1/3)^2
= -125 + 27 x 1/9
= -125 + 3
= -122
2014-09-10T17:01:59+02:00
A = - 22 + ( 10 - 36 x 2/9 )
A = - 22 + (10 - 72/9)
A = - 22 + (10 x 9 / 1 x 9 - 72/9)
A = 22 + (90/9 - 72/9)
A = 22 + 18/9
A = 22 x 9 / 1 x 9 + 18/9
A = 198/9 + 18/9
A = 216/9
A = 9 x 24 / 9 x 11
A = 24/11


B = 72 : 8 - 5 x 2
B = 9 - 10
B = - 1

C = (- 5)³ + 27 x (1/3)²
C = - 5³ + 27 x 1²/3²
C = - 125 + 27 x 1/9
C = - 125 + 27/9
C = - 125 x 9 / 1 x 9 + 27/9
C = 1125/9 + 27/9
C = 1152/9
C = 9 x 128 / 9 x 1
C = 128/1
C = 128